PERANAN SATUAN RESERSE KRIMINAL KEPOLISIAN DALAM MENANGGULANGI TINDAK PIDANA PENADAHAN KENDARAAN BERMOTOR DI POLRES SORONG - Fakaubun, Chaider; Morintoh, Raymond R.; Baho, Dayen (Ensiklopedia of Journal, 2024)
Abstract: The crime of theft is a chain crime, a criminal act that must take precedence over crime, because after someone commits a crime, the goods from the crime are used by themselves and some are used to be gifts and often used to attract profits, so the role of the police criminal investigation unit in tackling the crime of motor vehicle theft at the Sorong Police,  Then the obstacles experienced by the criminal investigation unit in tackling the crime of motor vehicle seizure at the Sorong Police. The research used is empirical juridical research that examines the applicable legal provisions and what happens in reality in society or research conducted on the actual situation that occurs in society, the data source in the preparation of this final project is carried out with primary legal materials, secondary legal materials and tertiary legal materials, data analysis is carried out after all the data from the results of this research is collected, the data is grouped into types and Source. The results of the research obtained by the role of the police are usually taken by the Criminal Investigation Unit in tackling the crime of motor vehicle seizure at the Sorong Police by collecting information about the case, including data on suspected vehicles, witnesses, and other evidence, investigations are carried out to find information about an event in this case the crime of theft, disguise as a prospective buyer of a motor vehicle, using false identities and interacting with suspects or syndicate members. The criminal investigation unit in tackling the crime of motor vehicle theft at the Sorong Police Station is a legal factor because the inconsistency and accuracy of legal regulations that regulate the crime of motor vehicle theft affects the investigation process, the limited personnel resources who can be assigned to investigate cases of motor vehicle theft can slow down the investigation process.Keywords: Sorong Police Force, Tackling, Motorized Vehicle Maintenance